High-temperature electrolysis of copper chloride using hybrid proton exchange membrane for hydrogen production - Ahmad Kamaroddin, Mohd Fadhzir (2022)
Comprehensive utilisation of green hydrogen energy is an excellent pathway to reduce greenhouse gas emissions and simultaneously eliminate the carbon footprint released into the atmosphere. Meanwhile, hydrogen production via CuCl thermochemical cycle is an attractive process due to moderate-/lowtemperature requirements and high efficiency. Therefore, there is a huge potential for producing hydrogen from the copper chloride (CuCl) thermochemical cycle by utilising the power plant's excess heat. Currently, the CuCl hydrogen electrolytic process is part of the CuCl thermochemical cycle. It produces hydrogen at low temperatures utilising the expensive Nafion and Nafion-based membranes. A high-temperature CuCl hydrogen electrolytic process using a hybrid membrane as the alternative membrane to Nafion for hydrogen production was performed in this study. A polybenzimidazole/zirconium phosphate (PBI/ZrP) hybrid membrane was synthesized using the solution mixing method followed by phosphoric acid (PA) doping. It was then validated for water uptake, tensile strength, thermogravimetric analysis (TGA), copper (Cu) diffusion and ionic exchange capacity (IEC). The PBI/ZrP hybrid membrane was developed after the screening process of PBI and sulphated poly (ether ether ketone) (SPEEK) membrane with the advantage of having high tensile strength (85.17 MPa), high ionic exchange capacity (3.2 × 10−3 mol g−1), low copper diffusion (7.87 × 10−7 cm2 s−1), sufficient water uptake (40 – 50 wt.%), a four-fold increase in proton conductivity compared to pristine PBI. The scanning electron microscope (SEM) was executed to evaluate the surface morphology of the membrane while SEMEDX detected the membrane’s composition. For the parametric study, the CuCl hydrogen electrolytic system with PBI/ZrP (0.5 A cm−2, 115 °C) produced 3.27 cm3 cm−1 hydrogen (highest). At a higher CuCl flowrate, the PBI/ZrP showed a significant increment of 66% (up to 3.27 cm3 min−1) when the applied current density was changed from 0.1 to 0.5 A cm−2. The CuCl hydrogen electrolytic process at 0.05 M CuCl concentration produced 2.69 cm3 min−1 and 2.15 cm3 min−1 hydrogen for PBI/ZrP and Nafion 117, respectively. The operating temperature (p = 0.026) and current density (p = 0.000) were found statistically significant based on the p-value < 0.05. The CuCl hydrogen electrolytic process parameters were optimised using a response surface method (RSM) with a central composite design (CCD). The optimised parameter settings were temperature at 116 °C, current density at 0.773 A cm−2 and CuCl concentration at 0.075 M to get the optimum hydrogen yield of 0.7167 cm3 min−1. The actual hydrogen yield from the optimized parameter settings was 0.7709 cm3 min−1 with a discrepancy of 7.56% from the predicted value. The high-temperature CuCl hydrogen electrolytic process using a PBI/ZrP hybrid membrane for hydrogen has been performed and proven a good alternative to Nafion. At the same time, able to yield maximum hydrogen output with optimum operating parameters, thus minimizing the associated cost in the hydrogen production.